What do pseudowords tell us about word processing? An overview - Martínez-Tomás, Celia; Baciero, Ana; Lázaro, Miguel; Hinojosa, José A. (Frontiers in Language Sciences, 2025)
This article provides an overview of the use of pseudowords—letter strings that resemble real words by adhering to phonotactic and orthotactic rules (e. g., fambo follows the rules of English phonology and orthography, but it does not have an actual meaning)—in written word processing research, with a focus on readers in alphabetic languages. We review how pseudowords have been used in research to isolate specific features of words to examine the cognitive mechanisms underlying various aspects of their processing, including orthographic, phonological decoding, lexical-semantic, and syntactic components, as well as to the way those empirical observations have shaped theories and models of word recognition. The overview also considers their broader applications, such as in studying non-alphabetic scripts, speech processing, and language disorders like dyslexia. By providing a focused synthesis of empirical findings, this article underscores the critical insights that research using pseudowords offers into the interconnected nature of cognitive mechanisms in language processing.